PEMBUATAN PAKAN KONSENTRAT DI KELOMPOK PETERNAK KELINCI MANDIRI DESA NGIJO KECAMATAN KARANGPLOSO KABUPATEN MALANG - Marhaeniyanto, Eko; Trisna Murti, Ariani; Susanti, Sri (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2017)
Production of rabbit can be improved through the availability of cheap feed. The solution offered is the manufacture of concentrated feed based on local ingredients. The availability of concentrate feed in the association of